2004
DOI: 10.2466/pr0.95.7.907-913
|View full text |Cite
|
Sign up to set email alerts
|

On Feeling Negative Past as a Part of Current Self: Subjective Temporal Organization of Autobiographical Memories

Abstract: When a past event is remembered, the subjective elapsed time is often different from the objective elapsed time, even if the exact date of an event is known. In this study, Feeling of Time Discrepancy between objective elapsed time and subjective elapsed time of turning point events was examined. Participants remembered one turning point event in life, dated the event, and estimated the Feeling of Time Discrepancy. Two groups, formed on their judgement of whether their present understanding of the event is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Shimojima (2002) demonstrated that although his participants knew the exact date of an event, and therefore the exact time passed since, they felt that subjectively more or less time has passed since that event, showing a discrepancy between the absolute and relative dating. Furthermore, Shimojima (2004) also demonstrated that emotionally charged events (i.e., whether negatively or positively valenced) would lead to discrepancies between absolute and relative dating, further supporting the disruptive effect of emotion. It is noteworthy that Hoerl and McCormack's model mentions that discrepancies have been observed between the reasoning and the updating system, which could be supported by Shimojima's study (2004).…”
mentioning
confidence: 74%
“…Shimojima (2002) demonstrated that although his participants knew the exact date of an event, and therefore the exact time passed since, they felt that subjectively more or less time has passed since that event, showing a discrepancy between the absolute and relative dating. Furthermore, Shimojima (2004) also demonstrated that emotionally charged events (i.e., whether negatively or positively valenced) would lead to discrepancies between absolute and relative dating, further supporting the disruptive effect of emotion. It is noteworthy that Hoerl and McCormack's model mentions that discrepancies have been observed between the reasoning and the updating system, which could be supported by Shimojima's study (2004).…”
mentioning
confidence: 74%
“…F .46; F .85; F 1.13, df 6/515, n.s., χ 2 7.93; χ 2 6.66; χ 2 7.42; χ 2 2.11, df 6, n.s. 508 Table 2 10 Table 3 Rating values of emotional evaluation for each category Fernandes et al, 2008;Mather & Carstensen, 2005Shimojima, 2004 Figure 2, Figure 3, Table 3 10 20…”
Section: Kruskal Wallismentioning
confidence: 99%